2014
DOI: 10.1371/journal.pone.0104069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Formaldehyde on Lymphocyte Subsets and Cytokines in the Peripheral Blood of Exposed Workers

Abstract: Formaldehyde (FA) is a well-known irritant, and it is suggested to increase the risk of immune diseases and cancer. The present study aimed to evaluate the distribution of major lymphocyte subsets and cytokine expression profiles in the peripheral blood of FA-exposed workers. A total of 118 FA-exposed workers and 79 controls were enrolled in the study. High performance liquid chromatography, flow cytometry, and cytometric bead array were used to analyze FA in air sample and formic acid in urine, blood lymphocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 46 publications
0
6
1
Order By: Relevance
“…The finding is in agreement with previous findings. 33 The exposure to the formaldehyde significantly ( P =0.0016) reduced the number of WBC of Chinese workers 34 which contradicts with the results of the present study. In order to eliminate possible confounding factors, 8 cases of confounding variables were excluded from the analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…The finding is in agreement with previous findings. 33 The exposure to the formaldehyde significantly ( P =0.0016) reduced the number of WBC of Chinese workers 34 which contradicts with the results of the present study. In order to eliminate possible confounding factors, 8 cases of confounding variables were excluded from the analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…The hematotoxicity of these chemicals, particularly for benzene and FA, has been investigated in other study populations. For FA, several studies in China have observed lower WBC counts in workers exposed to FA levels as low as 0.02-0.04 mg/m 3 (35), and significant alterations in platelets and lymphocyte subsets have also been reported in FA exposed workers although these findings have been less consistent (35)(36)(37)(38). The hematotoxicity of benzene exposure has been well-described as chronic exposure is associated with the development of various blood dyscrasias including aplastic anemia and myelodysplastic syndrome, even at relatively low levels of exposure (39).…”
Section: Discussionmentioning
confidence: 99%
“…The a temperature of 5 o C, this is because that the aniline polymerization process was an exothermic reaction, so a cold medium was needed to make slow polymeric structure [10]. This method can be done on a large scale with the results of PANI easily separated so that it was more flexible to use in the process of modification and application [11]. Subsequently, PANI-ES was carried out by developing using an ammonium base to obtain PANI-EB.…”
Section: Synthesis Polyaniline|graphitementioning
confidence: 99%
“…It is known that graphite promotes a better configuration for sensor devices, especially polyaniline [11]. The reason for achieving better results using graphite is related to improvements in the transfer of charge between polymers, graphite, and electrodes [1,4].…”
Section: Effects Of Variations In Graphite Composition On Polyaniline|graphite Compositesmentioning
confidence: 99%